The Role of Talent Management Practices in Enhancing the Creative Work Behavior of Employees - Imen bin Omar; Bushra Habib Hadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The current research aims to verify the relationship between talent management practices represented by (attracting talent, investing talent, localizing talent, retaining talent) and the creative work behavior of employees represented by (exploratory creative work behavior, investment creative work behavior), among a sample of teaching staff in private universities and colleges in the Middle Euphrates region, numbering (276) instructors. The researchers adopted the descriptive analytical approach, taking the questionnaire as a basic mechanism for collecting the necessary data for the practical aspect of the study. The study concluded that there is a relationship between talent management practices and the creative work behavior of employees. As a result, the study reached a set of recommendations, the most prominent of which is that private universities and colleges must create a flexible academic environment that encourages innovation, such as remote work options or flexible work schedules, which supports work-life balance and makes room for creative thinking, in addition to implementing a periodic evaluation system to measure the level of employee engagement and creative behavior, and using the evaluation results to improve programs and practices. Continuously.